Cephalotaxus griffithii Hook.f. needle extract induces cell cycle arrest, apoptosis and suppression of hTERT and hTR expression on human breast cancer cells - Moirangthem, Dinesh Singh (BioMed Central, 2014)
BACKGROUND: Cephalotaxus spp. are known to possess anticancer potential. In this present work, for the first time the effects of C. griffithii needle (CGN) extracts on human cancer cells were examined. METHODS: The CGN was successively extracted with petroleum ether (PE), acetone and methanol. The extracts were tested for its effect on proliferation of cancer cells (MTT assay on HeLa, ZR751 and HepG2). Extract that showed the maximum growth inhibitory effect was subjected for mechanism of action study. These included apoptosis (morphological and DNA fragmentation assay), cell cycle (flow cytometry), caspase expression (Western blot) and activity (assay kit), p53 (western blot and TP53 siRNA interference) and telomerase expression (reverse transcriptase PCR) analysis. RESULTS: Among the extracts, PE extract induced maximum cytotoxicity, with highest death occurred in ZR751 cells. Since, PE extract induced cell death was highest among the CGN extracts, with maximum cancer cell death occurred in ZR751 cells; we carried out mechanism study of PE extract induced ZR751 cell death. It was observed that PE extract induced ZR751 cell death was associated with cell cycle arrest and apoptosis by activating both intrinsic and extrinsic apoptotic pathways. Knock down study revealed that p53 is essential for loss of ZR751 cell viability induced by PE extract. Further, PE extract down-regulated hTERT, hTR, and c-Myc expression. Thin layer chromatography analysis indicated the presence of unique phytochemicals in PE extract. CONCLUSION: Based on the observations, we concluded that PE extract of C. griffithii needle contains important phyto-components with multiple cellular targets for control of breast cancer and is worthy of future studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1472-6882-14-305) contains supplementary material, which is available to authorized users.